Dielectric relaxation and resistive switching of Bi0.96Sr0.04Fe0.98Co0.02O3/CoFe2O4 thin films with different thicknesses of the Bi0.96Sr0.04Fe0.98Co0.02O3 layer. Issue 3 (15th February 2019) - Liu, Yun; Tan, Guoqiang; Chai, Zhengjun; Lv, Long; Yue, Zhongwei; Xue, Mintao; Ren, Huijun; Xia, Ao
Abstract: Bi0.96 Sr0.04 Fe0.98 Co0.02 O3 /CoFe2 O4 (BSFCO/CFO) bilayered thin films with different thicknesses of the BSFCO layer are synthesized on FTO/glass substrates by chemical solution deposition method (CSD). The influence of BSFCO thickness on the microstructure, dielectric relaxation, ferroelectric properties and resistive switching (RS) of the thin films are researched. Strain exists in the prepared thin films and gives rise to structural distortion, which has an effect on charged defects and ferroelectric polarization. Dielectric relaxation that is closely related to the interfacial polarization at the BSFCO/CFO interface is observed, and the dielectric loss peaks along with decreasing intensity shift to high frequency with decreasing strain. The Maxwell-Wagner two-layer model is adopted to investigate the mechanism of dielectric relaxation, and the relaxation time τ is calculated and it shown to be directly proportional to the strain. It is found that the dielectric properties, including low dielectric loss, can be improved by controlling the BSFCO layer thickness. The ferroelectric properties improve with the decreasing strain, the 12-BSFCO/CFO thin film possesses a large P r ~ 102.9 μC/cm 2 at 660 kV/cm. The observed resistive switching (RS) behavior is attributed to the interfacial conduction mechanism, it is found that strain-dependent the ferroelectric polarization switching modulates the width of depletion layer and the height of potential barrier at the interface, resulting in the different resistance states.